Construction of multilingual vocabulary: cultural perspectives - Biscalchin, Ricardo [UNESP]; Moreira, Walter [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2020)
Information Science seeks to organize and disseminate information in an effective, ethical and equally way. Breaking with linguistic and cultural barriers in accessing and representing information, through the construction of multilingual controlled vocabularies that follow the concepts of transculturality, multiculturality and cultural warranty is a way of meeting these objectives. The aim of this research is to present these concepts and demonstrate the importance of their application when building multilingual vocabularies for equal and fair access between different cultures. A theoretical analysis of technical standards and scientific publications on the subject was carried out to demonstrate the importance of the joint application of these concepts for the representation of information. This paper consists of discussing the importance of the relationship between these concepts, theories and norms for application in the construction of multilingual vocabularies, for a representation consistent with the socio-historical-cultural reality of the users. It is concluded that the application of transculturality, multiculturality and cultural guarantee in conjunction with the norms and scientific studies on the construction of multilingual vocabularies enables the terminological representation of information in each language, so that it contemplates the socio-historical-cultural context of each user, in an equally and fairly.
Keywords: Multilingual Controlled Vocabulary; Transculturality; Multiculturalism; Cultural Warranty; Knowledge Organization